Pengaruh Service Quality, Perceived Usefulness dan E-Banking terhadap Kepuasan Nasabah Bank BRI - Pratiwi, Anggun Anggraini Mila; Santoso, Adi; Setiawan, Fery (Ekonomis: Journal of Economics and Business, 2024)
The rapid growth of the banking industry in Indonesia has increased the level of competition between banks in terms of product innovation, service standards, technological system development and other banking services. The aim of this research is to determine the influence of service quality, perceived usefulness and e-banking on customer satisfaction. Bank BRI Ponorogo. The sample for this research was management study program students who used BRI Bank at Muhammadiyah University Ponorogo using snowball sampling techniques. The analysis used is multiple linear regression analysis. The results of this research found that service quality, perceived usefulness and e-banking have an influence on BRI bank customer satisfaction.